Dependability-oriented Multiobjective Optimization - Reinold, Peter; Sextro, Walter; Sondermann-Wölke, Christoph; Trächtler, Ansgar (Dependability of Self-Optimizing Mechatronic Systems)

Applications of Self-Optimizing Systems - Hölscher, Christian; Kessler, Jan Henning; Meyer, Tobias; Rasche, Christoph; Reinold, Peter; Sextro, Walter; Sondermann-Wölke, Christoph; Zimmer, Detmar (Dependability of Self-Optimizing Mechatronic Systems)

Impact and Influence Factors of Additive Manufacturing on Product Lifecycle Costs - Lindemann, C.; Jahnke, U.; Moi, M.; Koch, R. (24th Annual International Solid Freeform Fabrication Symposium)
At first sight the direct costs of Additive Manufacturing (AM) seem too high in comparison to traditional manufacturing. Considering the whole lifecycle costs of parts changes the point of view. Due to the modification of the new production process and new supply chains during a parts lifecycle, producing companies can strongly benefit from AM. Therefore, a costing model for assessing lifecycle costs with regard to specific applications and branches has been developed. The costing model represents the advantages of AM monetarily. For the evaluation of this model and the influence factors, different case studies have been performed including different approaches in part redesign. Deeper research is and will be carried out with respect to the AM building rates and the comparability of various AM machines, as these facts are hardly comparable for end users. This paper will present the methodology and some results of the case studies conducted over the whole product lifecycle.

The Need to Start Research Education Early - Joel, W. J. (IEEE Computer Graphics and Applications)

Information Visualization Courses for Students with a Computer Science Background - Kerren, A. (IEEE Computer Graphics and Applications)

Building Virtual Worlds Carrying on the Legacy of Randy Pausch's "Head Fake" - Schell, J.; Klug, C. (IEEE Computer Graphics and Applications)

The benefits of comics for language learning at the lower secondary level: A practical approach - Rumlich, Dominik (Teaching comics in the foreign language classroom)

Students’ general English proficiency prior to CLIL: Empirical evidence for substantial differences between prospective CLIL and non-CLIL students in Germany - Rumlich, Dominik (Content and language integrated learning (CLIL) in Europe)

Using comics in the classroom - The obvious way of creating a favourable learning environment? - Deane, Neil; Rumlich, Dominik (Medien und Interkulturalität im Fremdsprachenunterricht: Zwischen Autonomie, Kollaboration und Konstruktion)

A Variational Approach to Modeling Slow Processes in Stochastic Dynamical Systems - Noé, Frank; Nüske, Feliks (Multiscale Modeling & Simulation)

Some Investigations Regarding the Surface Treatment of Ultem 9085 Parts Manufactured with Fused Deposition Modeling - Fischer, M.; Schöppner, Volker (24th Annual International Solid Freeform Fabrication Symposium)
Fused Deposition Modeling (FDM) parts are typically subject to process-related rough or wavy surfaces, with stair-stepping effects whenever the parts produced have sloped or rounded part geometries; however, the level of optical quality frequently required demands that parts feature a smooth surface. In this paper, the results of a high-energy finishing process, which uses a disc finishing unit and is designed for parts manufactured with the material Ultem*9085, are presented. The analysis discusses the surface-smoothing effect of various finishing materials with varying geometries, as well as the effect of finishing time and speed. Additionally, the efficiency of the surface treatment has been analyzed specifically at corners, edges and in cavities.

Network of Information (NetInf) - An information-centric networking architecture - Dannewitz, Christian; Kutscher, Dirk; Ohlman, B; Farrell, Stephen; Ahlgren, Bengt; Karl, Holger (Computer Communications)

Improving Cooperative Transmission Feasibility by Network Reconfiguration in Limited Backhaul Networks - Dräxler, Martin; Biermann, Thorsten; Karl, Holger (International Journal of Wireless Information Networks)

Trade-off between latency and coverage in cooperative radio access networks - Hohenberger, Till; Herlich, Matthias; Karl, Holger (IEEE International Conference on Advanced Networks and Telecommunications Systems, ANTS 2013, Kattankulathur, India, December 15-18, 2013)

NetIDE: First Steps towards an Integrated Development Environment for Portable Network Apps - M. Facca, Federico; Salvadori, Elio; Karl, Holger; R. Lopez, Diego; Arranda Gutierrez, Pedro; Kostic, Dejan; Riggio, Roberto (Second European Workshop on Software Defined Networks, EWSDN 2013, Berlin, Germany, October 10-11, 2013)

Can service innovations substitute or complement product innovations? The case of German industrial firms - Eggert, A; Thiesbrummel, C; Deutscher, C (Proceedings of the 20th International Product Development Management Conference)

Increasing Customers' Willingness to Pay for Hybrid Offerings: The Impact of Price Presentation Formats - Eggert, A; Ulaga, W; Steiner, M; Backhaus, K (Proceedings of the 42nd European Marketing Academy (EMAC) Conference)

Threat and normative appeals to reduce product returns in online retailing – An effective marketing practice? - Garnefeld, I; Münkhoff, E; Raum, K (Proceedings of the 42nd European Marketing Academy (EMAC) Conference)

How to prolong a sales promotion – Ex-post time extension versus reframing - Münkhoff, E; Garnefeld, I; Bruns, A (roceedings of the 42nd European Marketing Academy (EMAC) Conference)

Creating Emotional Brand Attachment through the Salesperson's Brand-Consistent Behavior - Posner , T; Garnefeld, I; Eggert, A (Proceedings of the 42nd European Marketing Academy (EMAC) Conference)

The Effect of Loyalty Programs on Target and Bystander Customers: A Customer Portfolio Perspective on Loyalty Program Performance - Steinhoff, L; Palmatier, R. W (Proceedings of the 42nd European Marketing Academy (EMAC) Conference)

Exploring differential effects of product and service innovations on industrial firms’ financial performance - Eggert, A; Thiesbrummel, C; Deutscher, C (2013 AMA Winter Marketing Educators' Proceedings)

The playground of Wireless Dense networks of the future - Cicconetti, Claudio; Morelli, Arianna; Dräxler, Martin; Karl, Holger; Mancuso, Vincenzo; Sciancalepore, Vincenzo; Gupta, Rohit; de la Oliva, Antonio; Isabel Sanchez, M.; Serrano, Pablo; Roullet, Laurent (2013 Future Network & Mobile Summit, Lisboa, Portugal, July 3-5, 2013)

A topology-aware adaptive deployment framework for elastic applications - Keller, Matthias; Peuster, Manuel; Robbert, Christoph; Karl, Holger (17th International Conference on Intelligence in Next Generation Networks, ICIN 2013, Venice, Italy, October 15-16, 2013)

Energy-Efficient Assignment of User Equipment to Cooperative Base Stations - Herlich, Matthias; Karl, Holger (ISWCS 2013, The Tenth International Symposium on Wireless Communication Systems, Ilmenau, Germany, August 27-30, 2013)

Vorgehensmodelle 2013: Vorgehensmodelle - Anspruch und Wirklichkeit - Proceedings der 20. Tagung der Fachgruppe Vorgehensmodelle im Fachgebiet Wirtschaftsinformatik (WI-VM) der Gesellschaft für Informatik e.V., Lörrach (Germany)

Cross-layer scheduling for multi-quality video streaming in cellular wireless networks - Dräxler, Martin; Karl, Holger (2013 9th International Wireless Communications and Mobile Computing Conference, IWCMC 2013, Sardinia, Italy, July 1-5, 2013)

Anticipatory Buffer Control and Quality Selection for Wireless Video Streaming - Dräxler, Martin; Blobel, Johannes; Dreimann, Philipp; Valentin, Stefan; Karl, Holger (CoRR)

Ensuring Consistency Among Business Goals and Business Process Models - Nagel, Benjamin; Gerth, Christian; Post, Jennifer; Engels, Gregor (Proceedings of the 17th IEEE International EDOC Conference (EDOC'13))
The paradigm of service-oriented architectures has emerged as an architectural style for designing enterprise applications. Requirements engineering for such applications comprises the specification of business goal models representing stakeholder objectives and the operationalization to business process models that specify the required composition of services. Inconsistencies between business goals and derived business processes can lead to service compositions that are not in line with the actual stakeholder objectives. For preserving consistency it is required to consider logical and temporal dependencies among goals (e.g. the order in which they need to be achieved) in the derivation of business processes. In previous work, we provided a technique for the elicitation and specification of dependencies between business goals. Extending this approach, we aim at validating the consistency between business goal models and business process models regarding these dependencies. In this paper, we present a pattern-based approach for the automated generation of verifiable business process quality constraints from business goal models. We describe how these constraints can be used to check the consistency between business goals and business processes and demonstrate the applicability of our approach in a case study by using the implemented tool support.

Modellbasierte Bewertung von Testprozessen nach TPI NEXT® mit Geschäftsprozess-Mustern - Schumacher, Claudia; Engels, Gregor; Güldali, Baris; Niehammer, Markus; Hamburg, Matthias (Proceedings of the conference on Software Enginneering, Fachtagung des GI Fachbereichs Softwaretechnik (SE 2013), Aachen (Germany))

On-the-Fly Computing - Das Entwicklungs- und Betriebsparadigma für Softwaresysteme der Zukunft - Engels, Gregor (Software Engineering 2013)

Automated Service Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the 11th International Conference on Service Oriented Computing (ICSOC'13))

High-Quality Specification of Self-Adaptive Software Systems - Luckey, Markus; Engels, Gregor (Proceeding of the 8th international symposium on Software engineering for adaptive and self-managing systems)

Decision Support via Automated Metric Comparison for the Palladio-based Performance Blame Analysis - Brüseke, Frank; Becker, Steffen; Engels, Gregor (Proceedings of the 4th ACM/SPEC International Conference on Performance Engineering (ICPE 2013), Prague (Czech Republic))

Performance Analysis of Self-Adaptive Systems for Requirements Validation at Design-Time - Becker, Matthias; Luckey, Markus; Becker, Steffen (Ninth International ACM Sigsoft Conference on the Quality of Software Architectures)

Integrating Coverage Analysis into Test-driven Development of Model Transformations - Küster, Jochen; Kovács, Dániel; Bauer, Eduard; Gerth, Christian

Automated Service Discovery and Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor

Sicherheitsherausforderungen in hochverteilten Systemen - de Meer, Hermann; Diener, Michael; Herkenhöner, Ralph; Kucera, Markus; Niedermeier, Michael; Reisser, Andreas; Schryen, Guido; Vetter, Michael; Waas, Thomas; Yasasin, Emrah (PIK - Praxis der Informationsverarbeitung und Kommunikation)

High Tech and High Touch: A Framework for Understanding User Attitudes and Behaviors Related to Smart Interactive Services. - Wünderlich, Nancy; Wangenheim, Florian V; Bitner, Mary Jo (Journal of Service Research)
Smart interactive services, in contrast with other technology-based services, require significant human-to-human interaction and collaboration in addition to the service provided by the embedded technology itself. The authors’ foundational Delphi study confirms smart interactive services (e.g., remote diagnosis, remote repair of equipment, and telemedicine) are a rapidly growing innovation category across industries. Yet, gaining user acceptance of these types of services presents a significant challenge for managers. To address this challenge, the authors employ a grounded theory approach, drawing on depth interviews, to develop a framework of barriers and facilitators to users’ attitudinal and behavioral responses to smart interactive services. The findings reveal a new set of beliefs that are critical in this context. These beliefs are tied to the human element and specifically pertain to beliefs about the “service counterpart (SC),” who is the provider’s employee controlling the technology. Control, trustworthiness, and collaboration beliefs emerge jointly as important and interrelated influencers tied to the SC. Contrary to conventional wisdom that focuses on features of the technology itself to gain user acceptance, this research encourages providers to emphasize the interpersonal elements of the service by providing control cues, raising social presence, and enhancing human trust mechanisms.
Keywords: service technology; technology-mediated service; service counterpart; smart service; remote service; technology adoption

Konzeption modellbasierter Benutzungsschnittstellen für verteilte Selbstbedienungssysteme - Yigitbas, Enes; Gerth, Christian; Sauer, Stefan (Informatik 2013, 43. Jahrestagung der Gesellschaft für Informatik e.V. (GI), Informatik angepasst an Mensch, Organisation und Umwelt, 16.-20. September 2013, Koblenz, Deutschland)

Releasing multimodal data as Linguistic Linked Open Data: An experience report - Menke, Peter; McCrae, John; Cimiano, Philipp (Proceedings of the 2nd Workshop on Linked Data in Linguistics (LDL-2013): Representing and linking lexicons, terminologies and other language data)

Editorial: Internationales Personalmanagement: Den kulturellen Kontext gestalten - Kabst, Rüdiger; Wehner, M C (PERSONALquartely)

Unterstützung von Kommunalverwaltung bei Bürgerbeteiligung - Weber, P; Kabst, Rüdiger (Verwaltungskommunikation - Wissenschaftliche Analyse und praktische Beispiele)

Effektiver Einsatz von Rettungskräften bei Naturkatastrophen - Modelle und Verfahren zur Entscheidungsunterstützung - Wex, Felix; Schryen, Guido (Blick in die Wissenschaft)

Institutional Determinants of Work-Family Practices: An International Comparative Examination. - Weber, H; Wehner, M; Kabst, Rüdiger

HR-Praktiken und Innovation: Wie können Wissens- und Technologievorsprünge im Unternehmen generiert werden? - Golubovic, S; Wehner, M; Baum, M; Kabst, Rüdiger

Institutional Pressures and Interorganizational Imitation: A Quasilongitudinal Analyses of Temporary Work in the UK and Germany - Isidor, R; Wehner, M; Li, C; Kabst, Rüdiger

A Taxonomy-Based Approach towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard (Distributed, Ambient, and Pervasive Interactions)

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten (Design, User Experience, and Usability. Design Philosophy, Methods, and Tools)

Do You Speak Usability? - Aktueller Stand des Glossars und des Curriculums für den Certified Professional for Usability and User Experience (CPUX) der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter (Jahresband Usability Professionals)